Pay-to-Play: An Examination of State Laws. (31st July 2017) - Bromberg, Daniel; Hartley, Roger E.; Mohammed-Spigner, Deborah
Abstract : Laws regulating how government contractors participate in political campaign spending, commonly referred to as pay-to-play (P2P) laws, are emerging throughout the United States. As of 2015, there were 17 states with P2P laws of some type, most commonly disclosure requirements and restrictions on campaign spending by government contractors. Although such laws, regulations, and executive orders are becoming more prevalent, our understanding of their characteristics remains limited. This article provides a foundational framework that can be applied to systematically assess P2P laws using the dimensions of coercion and specificity. The authors classify each state based on these two categories. The findings suggest that U.S. states are neither specific in their laws nor have coercive penalties for those who break the law.